Assessing the influence of multimedia instruction on knowledge transfer in higher education: Multimodal learning experiences - Bernadetha Haule, Daigo; Shaker, Thanaa; Nkwera, Godfrey Yohanes (Indonesian Journal of Education and Pedagogy, 2024)
This study investigates the impact of multimedia instruction on knowledge transfer in higher education. Focused on the evolution from traditional lecture-based methods to interactive approaches, the research conducted at the Indonesian International Islamic University with postgraduate students highlights live demonstrations as the preferred multimedia tool, perfectly aligning with the practical nature of postgraduate education. The key findings underscore the integral role of technological infrastructure and teacher training in ensuring successful multimedia integration. Notwithstanding challenges such as curriculum misalignment and resistance to change, the study emphasizes the overwhelmingly positive impact of multimedia on learning outcomes. This insight offers crucial considerations for refining postgraduate curricula, strategically investing in technology, and promoting faculty development initiatives. The intricate interplay among technological infrastructure, teacher expertise, and curriculum alignment stresses the imperative of a holistic strategy. Implications extend to aligning multimedia content with student preferences, investing in robust institutional support, and recognizing the potential for personalized learning through multimedia tools. The study advocates for the strategic integration of visual and interactive elements in education, urging universities to embrace multimedia for optimal instructional outcomes and preparing students for modern world complexities, offering valuable insights for educators, instructional designers, and policymakers.